Effects of psychological distance perception and psychological factors on pro-environmental behaviors in Taiwan: Application of construal level theory - Chen, Mei-Fang (International Sociology)
This study applied construal level theory (CLT) to the perceived psychological distance of climate change to investigate Taiwanese people$1 (Bs psychological distance perception of climate change. It also considered how this psychological distance perception of climate change and other crucial psychological factors (i.e., values, ecological worldviews, and environmental concerns) may influence people$1 (Bs pro-environmental behaviors (PEBs). A national self-administered questionnaire survey was performed in Taiwan and 733 responses were analyzed empirically. Structural equation modeling analysis indicated that an individual$1 (Bs altruistic values are positively related to his or her ecological worldviews. An individual$1 (Bs ecological worldviews are positively related to his or her psychological distance perception of climate change and environmental concerns regarding the negative consequences of climate change. Such environmental concerns positively motivate engagement in PEBs. However, an individual$1 (Bs psychological distance perception of climate change does not positively relate to his or her PEBs. - Reproduced.s
Keywords: Environment - Taiwan